Description of Hb Évora (HBA2: c.106T>C) on an Unexpected Allele in a Swiss Family. (3rd September 2021) - Truttmann, Rahel; Schmidt, Adrian; Hartmann, Britta; Rusch, Sebastian; Mendez, Adriana
Abstract: α-Thalassemia (α-thal) is caused by DNA deletions or point mutations in the genes coding for the α-globin chains and can lead to hemolytic anemia in its carriers. If only one of the four α genes is affected, the mutation is mostly discovered by chance, as the carriers are asymptomatic. Hb Évora ( HBA2 : c.106T>C) is an Hb variant that leads to such an α-thal trait (α T α/αα) and thus, to mild microcytic hypochromic anemia. The mutation was first reported in 2001 and named Hb Évora in 2007 (based on the geographic origin of one of the studied families). It was found in four unrelated families originating from Portugal and the Philippines. We now report the discovery of Hb Évora not only in a proband with no known ancestors from either country, but also on an unexpected allele. Subsequently, her close relatives were studied, revealing the same mutation in her brother. No clear correlation between phenotype and genotype was observed.